2023
DOI: 10.2174/1568009622666220705101642
|View full text |Cite
|
Sign up to set email alerts
|

Epigallocatechin-3-gallate Induced HepG2 Cells Apoptosis through ROSmediated AKT /JNK and p53 Signaling Pathway

Abstract: Background: Hepatocarcinoma is the third leading cause of cancer-related deaths around the world. Recently, some studies have reported that Epigallocatechin-3-gallate (EGCG) may have the potential for anti-cancer. However, the affection and putative mechanisms of cytotoxicity induced by EGCG in HepG2 cells remain unknown. Based on the above, the present study evaluated the effect of EGCG on the cytotoxic and anti-cancer mechanisms on HepG2 cells. Methods: The effect of EGCG on the apoptosis of Hep-G2 cells a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 45 publications
0
1
0
Order By: Relevance
“…It was shown that a prolonged activation of ERK induced cell apoptosis [ 170 ]. Moreover, when EGCG was applied to a hepatocarcinoma cell line (HepG2), its proapoptotic activity was stimulated by the JNK pathway [ 190 ]. However, in a study on human bladder cancer cells (T24), a 30 min pretreatment with EGCG before the application of IL-1β caused the suppression of both the ERK1/2 and JNK pathways by silencing their transcriptional activity, while EGCG, in a concentration range of 0–50 μM, did not affect the T24 cells’ viability [ 191 ].…”
Section: Mechanism Of Anticancer Activity Of Egcgmentioning
confidence: 99%
“…It was shown that a prolonged activation of ERK induced cell apoptosis [ 170 ]. Moreover, when EGCG was applied to a hepatocarcinoma cell line (HepG2), its proapoptotic activity was stimulated by the JNK pathway [ 190 ]. However, in a study on human bladder cancer cells (T24), a 30 min pretreatment with EGCG before the application of IL-1β caused the suppression of both the ERK1/2 and JNK pathways by silencing their transcriptional activity, while EGCG, in a concentration range of 0–50 μM, did not affect the T24 cells’ viability [ 191 ].…”
Section: Mechanism Of Anticancer Activity Of Egcgmentioning
confidence: 99%